Parameters affecting antiradical, elemental composition and microstructural elucidation in the heat reflux extraction of dried piper nigrum seedlings - Olalere, Olusegun Abayomi; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth (Ahvaz Jundishapur University of Medical Sciences, 2019)
Background: Black- and white pepper extracts are natural products, which had been extensively used in food industries as a seasoning agent, and in herbal medicine for the treatment of many free radical-related diseases. Owing to the medicinal and nutritive benefits of this functional spice, the need then arises to find a way of extracting its fixed oil at optimum condition. Objectives: The aim of this study was to investigate the effect of extraction parameters on the extraction yield, antioxidant activities, microstructure, functional group characteristics, and elemental composition of fixed oils extracted from the two cultivars. Methods: Extraction of fixed oil was carried out using a heat reflux extraction technique. The dietary elemental composition was conducted using Energy Dispersive Spectroscopy (EDS). The effect of localized heating on the extracts was evaluated to determine the structural changes in the pepper sample using Brunauer-Emmett-Teller (BET) and Scanning Electron Microscopy (SEM). Results: The optimal fixed oil yields under the optimum condition were 10.38 mg/g for the black pepper and 15.27 for the white pepper. The antiradical powers (ARP) of 0.007985 and 0.009046 mL/µg were obtained for black- and white pepper fixed oil, respectively. This suggests that the fixed oil from white pepper exhibited higher antiradical characteristics than black pepper fixed oil. The results of BET-parameters revealed the percentage of deformations related to the black- and white pepper under the localized heating was 21.47% and 29.14%, respectively. Conclusions: The results revealed a greater deformation on the microstructure of white pepper than black pepper. Moreover, rich dietary elements present in the extracts succinctly unveiled the potential of fixed oil extracts in curative applications and preventive traditional medicine.